Fully-polished glazed tile with deep and continuous concave textures and preparation method of fully-polished glazed tile
Through the combination of glaze-polished and dry-grain glaze of high silicon, high aluminum and low flux system, the problems of fully polished glazed tiles in taking into account hardness, wear resistance and stain resistance are solved, and deep continuous depression texture and excellent stain resistance are achieved. performance.
Patent Information
- Application Number
- CN202411373952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
While maintaining the three-dimensional recessed texture, existing fully polished glazed tiles are difficult to take into account both hardness, wear resistance and stain resistance, and the recessed texture lines are prone to discontinuous or green.
The glaze-plated with high silicon, high aluminum, low flux system is combined with dry-grain glaze. The texture depth and line continuity are maintained through the low and high temperature flowability of glaze, and the high hardness and permeability of dry-grain glaze are improved. Abrasive and antifouling.
The deep continuous depression texture of fully polished glaze tiles is achieved, which improves hardness, wear resistance and anti-fouling performance, and ensures the smoothness and smoothness of the glaze and anti-fouling effect.
Smart Images

Figure BDA0005068255660000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building ceramics, and in particular to a fully polished glazed tile with deep and continuous concave textures and a preparation method thereof. Background Art
[0002] With the continuous development of social economy and the significant improvement of people's living standards, consumers' choice of decorative materials is no longer limited to practicality, but they pay more attention to their decorative and artistic sense, which has brought unprecedented changes to the decorative materials market. Among them, tiles with three-dimensional sunken texture effects are increasingly winning market favor and praise with their unique visual effects, rich layering and the ability to create spatial depth and three-dimensionality.
[0003] In the prior art, tiles with three-dimensional concave texture effects can generally be prepared by the following two methods:
[0004] (1) Use oily mold / carving ink and water-based glaze (such as polishing glaze) to physically repel each other to form a concave-convex texture. The polishing glaze in the prior art usually has a lower high-temperature viscosity (i.e., better high-temperature fluidity), so that the bubbles generated during the calcination process can be discharged smoothly, ensuring the transparency and anti-fouling performance of the fully polished glaze. At the same time, since the polishing glaze has good high-temperature fluidity, when the amount of polishing glaze applied is too much, its fluidity will be further enhanced, thereby partially or completely filling the gap between the mold / carving ink and the polishing glaze, weakening the concave-convex effect. Therefore, the amount of polishing glaze applied in the prior art is generally small. However, the polishing glaze with a small amount of application will limit the depth of the concave-convex texture formed by the physical repulsion between the oily mold / carving ink and the polishing glaze. In order for the fully polished glazed tiles to present a mirror-like gloss effect after polishing, the glazed tiles need to be polished to a certain thickness, resulting in the concave-convex texture with limited depth being prone to discontinuous concave lines after polishing.
[0005] (2) The effective ingredients in the sinking ink (such as chromium salts) can react with divalent ions such as calcium, magnesium, and zinc in the polishing glaze at high temperatures, thereby forming a sunken texture on the surface of the glaze layer. The polishing glaze formula used in conjunction with the sinking ink generally contains more divalent ions such as calcium, magnesium, and zinc. Although a high content of divalent ions is beneficial to ensure anti-fouling performance, it will also lead to a reduction in the content of silicon and aluminum in the polishing glaze, which will reduce the hardness and wear resistance of the polishing glaze, thereby reducing the hardness and wear resistance of the glazed tile glaze; in addition, due to the presence of a high content of divalent ions, the melting temperature of the polishing glaze is relatively low, and it has a certain fluidity at high temperatures, resulting in the partial melting of the sunken texture, so that the depth of the formed sunken texture is limited, which also leads to the discontinuity of the sunken texture lines after full polishing. In addition, since the sinking ink generally contains chromium salts, the chromium salts will generate chromium pentoxide during the reaction process, which can easily cause the sunken texture to turn green, thereby affecting the color of the glazed tile.
[0006] In summary, tiles with three-dimensional sunken texture effects generally have problems such as discontinuous lines and green lines. It is difficult for the glaze to take into account hardness, wear resistance and stain resistance at the same time, and it is difficult to meet actual usage needs. Summary of the invention
[0007] The purpose of the present invention is to propose a method for preparing fully polished glazed tiles with deep and continuous concave textures. On the premise that the glazed tiles can meet the full polishing requirements, the present invention solves the problems of discontinuous lines and green lines of existing fully polished glazed tiles, and the difficulty of the glaze surface to simultaneously take into account the hardness, wear resistance and anti-fouling properties, so as to meet actual use needs.
[0008] Another object of the present invention is to provide a fully polished glazed tile with deep and continuous concave texture, wherein the glaze surface has deep and continuous concave texture and also has excellent hardness, wear resistance and stain resistance.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] A method for preparing a fully polished glazed tile with a deep and continuous concave texture comprises the following steps:
[0011] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0012] B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer;
[0013] C. Sprinkling polishing glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the polishing glaze includes SiO2 62-66%, Al2O3 13-16%, CaO 4-7%, MgO 0-2%, K2O 0-1%, Na2O 4-6%, BaO 0-2%, SrO 3-5% and ZnO 3-5%, and the rest is loss on ignition;
[0014] D. spraying dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include dry granules, flux and suspending agent;
[0015] E. After drying, put it into the kiln for firing, and after full polishing, you can get fully polished glazed tiles.
[0016] Furthermore, in step C, the glaze is passed through a 250-mesh sieve, the residue is 0.3-0.5% and the viscosity is 2000-3000 mPa·s according to mass percentage.
[0017] Furthermore, in step C, the specific gravity of the glaze is 1.85-1.87, and the glaze pouring amount is 448-530 g / m 2 .
[0018] Furthermore, calculated by weight, the raw materials for the glaze include 55-60 parts of albite, 8-12 parts of dolomite, 6-10 parts of washed kaolin, 5-8 parts of strontium carbonate, 10-12 parts of quartz, 3-5 parts of zinc oxide, 4-8 parts of calcite and 1-3 parts of calcined alumina.
[0019] Furthermore, in step D, the mixing ratio of the dry particles, the flux and the suspending agent is (17-26): (21-33): (6-10) in terms of mass ratio.
[0020] Further, in step D, the dry particles include quartz, corundum and alumina; the flux includes potassium feldspar, wollastonite, zinc oxide and barium carbonate; the suspending agent includes washed kaolin;
[0021] Calculated by weight, the raw materials of the dry granular glaze include 13 to 18 parts of quartz, 1 to 3 parts of corundum, 3 to 5 parts of aluminum oxide, 6 to 10 parts of washed kaolin, 36 to 42 parts of potassium feldspar, 15 to 20 parts of wollastonite, 6 to 10 parts of zinc oxide and 0 to 3 parts of barium carbonate.
[0022] Furthermore, in step D, the specific gravity of the dry granular glaze is 1.20-1.25, and the spraying amount of the glaze is 122-163 g / m 2 .
[0023] Furthermore, in step D, the specific method of the full polishing treatment is: firstly, the surface of the glazed tile is roughly polished using the diamond grinding block group I, then the surface of the glazed tile is medium polished using the diamond grinding block group II, and finally the surface of the glazed tile is finely polished using the diamond grinding block group III;
[0024] Among them, the weight of the corundum grinding blocks in the corundum grinding block group I is greater than the weight of the corundum grinding blocks in the corundum grinding block group II, and the weights of the corundum grinding blocks in the corundum grinding block group II and the corundum grinding block group III are the same; the mesh number of the corundum grinding blocks in the corundum grinding block group I is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group II, and the mesh number of the corundum grinding blocks in the corundum grinding block group II is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group III.
[0025] Further, in step D, the diamond grinding block group I includes 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 220 to 240, 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 280 to 300, and 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 380 to 400;
[0026] The diamond grinding block group II includes 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 550 to 600 meshes and 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 780 to 800 meshes;
[0027] The diamond grinding block group III includes 5 to 10 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1000 to 1100, 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1400 to 1500, and 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1800 to 2000.
[0028] A fully polished glazed tile with deep and continuous concave texture is prepared using the above-mentioned method for preparing a fully polished glazed tile with deep and continuous concave texture. The wear resistance of the fully polished glazed tile reaches at least level 4 2100 revolutions, and the anti-fouling level reaches level 5.
[0029] The technical solution provided by the present invention may include the following beneficial effects:
[0030] 1. This technical solution adopts a high-silicon, high-aluminum, low-flux system of glaze, which makes the glaze have lower high-temperature fluidity, avoids the glaze flowing during the firing process and filling the grooves formed by the mold texture, and makes the glaze not easy to melt flat during the kiln firing process, and still maintains its three-dimensional state, ensuring the depth of the sunken texture and the continuity of the lines. At the same time, because this technical solution uses the mold ink to physically push away the glaze to form a sunken texture, rather than using the sunken ink to chemically react with the glaze to form a sunken texture, it avoids the occurrence of the situation where the sunken texture is easily turned green by using the sunken ink. In addition, because the higher the silicon and aluminum content in the glaze formula, and the lower the content of flux such as magnesium oxide, calcium oxide and zinc oxide, the sunken texture layer formed after the glaze is fired has higher hardness and wear resistance. In addition, in the present technical solution, due to the lower high-temperature fluidity of the glaze, the glaze has a higher high-temperature viscosity, which is beneficial to slow down the movement speed of bubbles in the recessed texture layer, so that the bubbles remaining in the calcination process mainly stay in the middle and lower layers of the glazed tiles after calcination, so that during the full polishing process, the bubbles remaining in the brick body will not burst and form micropores, which is beneficial to ensure the smoothness and flatness of the glaze surface, thereby ensuring the anti-fouling performance.
[0031] 2. This technical solution adopts the method of first pouring polishing glaze and then spraying dry granular glaze to replace the existing wear-resistant dry granular polishing glaze. The dry granular glaze has the characteristics of both transparency and anti-fouling, which is conducive to improving the anti-fouling and transparency of glazed tiles. At the same time, the polishing glaze makes the bubbles remaining in the calcination process mainly stay in the middle and lower layers of the polished glazed tiles after calcination, avoiding the rupture of bubbles during the polishing process and affecting the anti-fouling performance. In addition, the dry granular glaze layer formed by the dry granular glaze protects the concave texture layer formed by the polishing glaze, further ensuring that even if there are bubbles in the concave texture layer, the above bubbles will not rupture to form micropores during the polishing process and affect the anti-fouling performance of the glaze surface, thereby further ensuring the anti-fouling performance. DETAILED DESCRIPTION
[0032] The present technical solution provides a method for preparing a fully polished glazed tile with a deep and continuous concave texture, comprising the following steps:
[0033] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0034] B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer;
[0035] C. Sprinkling polishing glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the polishing glaze includes SiO2 62-66%, Al2O3 13-16%, CaO 4-7%, MgO 0-2%, K2O 0-1%, Na2O 4-6%, BaO 0-2%, SrO 3-5% and ZnO 3-5%, and the rest is ignition loss;
[0036] D. spraying dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include dry granules, flux and suspending agent;
[0037] E. After drying, put it into the kiln for firing, and after full polishing, you can get fully polished glazed tiles.
[0038] In order to solve the problems of discontinuous lines and green lines in the preparation of fully polished glazed tiles with concave textures in the prior art, and the difficulty of the glaze surface to simultaneously take into account hardness, wear resistance and anti-fouling properties, this technical solution proposes a method for preparing fully polished glazed tiles with deep and continuous concave textures, including five steps: A (blank making), B (printing fine carving ink), C (pouring glaze), D (spraying dry granular glaze) and E (firing in the kiln). Through the mutual cooperation of glazing and dry granular glaze, the glaze surface not only has continuous and deep concave textures, but also has excellent hardness, wear resistance and anti-fouling properties to meet the use requirements. It should be noted that the blank in this solution is made by pressing and drying conventional ceramic blanks in the ceramic field, and the ceramic blanks are not further described here.
[0039] Specifically, in the prior art, tiles with three-dimensional sunken textures can generally be prepared by the following two methods: (1) using oily molds / carving inks and water-based glazes (such as polished glazes) to physically separate them to form a concave-convex texture, but the above method of preparing textures is difficult to take into account both anti-fouling performance and line continuity. (2) using the active ingredients in the sunken ink (such as chromium salts) to react with divalent ions such as calcium, magnesium, and zinc in the polished glaze at high temperatures to form a sunken texture, but the above method of preparing sunken textures has problems such as discontinuous lines, green lines, and it is difficult for the glaze surface to take into account hardness, wear resistance, and anti-fouling performance at the same time.
[0040] In order to solve the above defects, the technical solution adopts a high-silicon, high-aluminum, low-flux system of polishing glaze, so that the polishing glaze has lower high-temperature fluidity, avoids the polishing glaze flowing during the firing process and filling the gullies formed by the mold texture, and makes the polishing glaze not easy to melt flat during the kiln firing process, and still maintains its three-dimensional state, ensuring the depth of the sunken texture and the continuity of the lines. At the same time, because the technical solution uses the mold ink to physically push away the polishing glaze to form a sunken texture, rather than using the sunken ink to chemically react with the polishing glaze to form a sunken texture, it avoids the occurrence of the situation where the sunken texture is easily greened by using the sunken ink. In addition, because the higher the silicon and aluminum content in the polishing glaze formula, and the lower the content of flux such as magnesium oxide, calcium oxide and zinc oxide, the sunken texture layer formed after the polishing glaze is fired has higher hardness and wear resistance. In addition, in the present technical solution, due to the lower high-temperature fluidity of the glaze, the glaze has a higher high-temperature viscosity, which is beneficial to slow down the movement speed of bubbles in the recessed texture layer, so that the bubbles remaining in the calcination process mainly stay in the middle and lower layers of the glazed tiles after calcination, so that during the full polishing process, the bubbles remaining in the brick body will not burst and form micropores, which is beneficial to ensure the smoothness and flatness of the glaze surface, thereby ensuring the anti-fouling performance.
[0041] It should be noted that, in the present technical scheme, the chemical composition of the polishing glaze, calculated by mass percentage, includes SiO2 62-66%, Al2O3 13-16%, CaO 4-7%, MgO 0-2%, K2O 0-1%, Na2O 4-6%, BaO 0-2%, SrO 3-5% and ZnO 3-5%. By limiting the content of SiO2 and Al2O3 in the polishing glaze, it is ensured that the polishing glaze will not be completely devitrified and not colorized, while the thickness of the polishing glaze is large enough to meet the full polishing requirements.
[0042] Furthermore, although the polishing glaze with lower high temperature fluidity can form a continuous and deep concave texture with the mold ink, the depth of the concave-convex texture is limited, which is difficult to meet the needs of deeper textures. Therefore, the technical solution sprays the dry granular glaze after pouring the polishing glaze. The dry granular glaze introduces dry particles to increase the depth of the mold texture, thereby increasing the depth and continuity of the concave texture, making the glazed tile more concave and convex, so as to meet the actual use needs.
[0043] In addition, the high hardness and high wear resistance of the dry particles themselves are conducive to significantly improving the hardness and wear resistance of the glaze. At the same time, the dry particle glaze also reduces the calcination temperature of the dry particle glaze by adding flux, so that the dry particle glaze forms a certain amount of glass on the premise of improving the depth of the concave texture and the continuity of the lines, covering the surface of the concave texture layer, ensuring the transparency and anti-fouling performance of the glaze. In addition, the addition of suspending agent is conducive to the uniform dispersion of dry particles in the glaze layer, increasing the accumulation depth of dry particles, and effectively avoiding the agglomeration and precipitation of dry particles, which leads to the whitening of the glaze surface, which not only ensures the transparency effect of the glaze, but also ensures the consistency of hardness, wear resistance and anti-fouling properties of the glaze.
[0044] Therefore, the dry particle glaze of the present technical solution can not only enhance the depth and line continuity of the concave texture of the glazed tile by adding dry particles, flux and suspending agent, but also help to ensure the hardness, wear resistance, stain resistance and transparency of the glaze surface.
[0045] It should be noted that in the prior art, polishing glaze and dry particles are generally used to form wear-resistant dry particle polishing glaze, but the glaze layer obtained by the wear-resistant dry particle polishing glaze is generally thicker, and the high-temperature viscosity of the wear-resistant dry particle polishing glaze is relatively large, so that there may be more bubbles in the glaze layer, resulting in the bubbles being easily broken during the polishing process and forming micropores on the glaze surface, which become a hiding place for dirt and stains, affecting the anti-fouling performance. In addition, since the content of dry particles in the glaze layer obtained by the wear-resistant dry particle polishing glaze is relatively high, and the dry particles are easy to scatter or absorb part of the light, resulting in a decrease in the transparency of the glaze layer.
[0046] This technical solution adopts the method of first pouring polishing glaze and then spraying dry granular glaze to replace the existing wear-resistant dry granular polishing glaze, and utilizes the characteristics of dry granular glaze that has both transparency and anti-fouling properties, which is conducive to improving the anti-fouling and transparency of glazed tiles; at the same time, the polishing glaze makes the bubbles remaining in the calcination process mainly stay in the middle and lower layers of the polished glazed tiles after calcination, avoiding the rupture of bubbles during the polishing process and affecting the anti-fouling performance. In addition, the dry granular glaze layer formed by the dry granular glaze protects the concave texture layer formed by the polishing glaze, further ensuring that even if there are bubbles in the concave texture layer, the above bubbles will not rupture to form micropores during the polishing process and affect the anti-fouling performance of the glaze surface, thereby further ensuring the anti-fouling performance.
[0047] Preferably, in step C, calculated by mass percentage, the chemical composition of the glaze includes SiO2 63%, Al2O3 14%, CaO 5%, MgO 1%, K2O 0.5%, Na2O 5%, BaO 1%, SrO 4% and ZnO 4%, and the rest is loss on ignition.
[0048] This technical solution adds SiO2 and Al2O3 content up to 67% to the polishing glaze formula, which is conducive to making the polishing glaze have lower high-temperature fluidity, thereby ensuring the depth of the concave texture and the continuity of the lines. At the same time, the addition amount of CaO, MgO, K2O, Na2O, BaO, SrO and ZnO with fluxing effect in the formula is limited to ensure that the polishing glaze has a certain sense of transparency and color development performance.
[0049] Preferably, the method further comprises step F and step G, and step F and step G are located between step A and step B;
[0050] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0051] F. Applying base glaze on the surface of the body to form a base glaze layer;
[0052] G. Printing color ink on the surface of the base glaze layer according to a preset pattern to form a pattern texture layer;
[0053] B. Printing mold ink on the surface of the pattern texture layer according to a preset pattern to form a mold ink layer.
[0054] In one embodiment of the present technical solution, a step of applying a base glaze and a step of printing a color ink are added between the step of making a blank and the step of printing a mold ink. The setting of the base glaze layer can cover the ceramic blank, prevent the blank from affecting the pattern texture of the color ink, and help to further enhance the color effect of the pattern texture layer. It should be noted that the base glaze in the present technical solution can be prepared from an existing base glaze formula that can cover the color of the blank, and the mold ink layer is printed from conventional mold ink in the ceramic field. The base glaze and mold ink are not further described here.
[0055] Preferably, the glaze amount of the base glaze is 408-490 g / m 2 , which can effectively ensure the covering effect of the base glaze; the specific gravity of the base glaze is 1.85-1.87, and the flow rate of the base glaze is 25-45 mL / s, which is conducive to ensuring uniform coating of the base glaze on the surface of the blank.
[0056] Further, in step C, according to the mass percentage, the glaze passes through a 250-mesh sieve, the residue is 0.3-0.5%, and the viscosity is 2000-3000 mPa·s.
[0057] In a preferred embodiment of the present scheme, in order to obtain a better sunken texture effect, the present technical scheme adjusts the fineness of the polished glaze so that it passes through a 250-mesh sieve with a residue of 0.3 to 0.5%, which is beneficial to ensuring the performance of the polished glaze; at the same time, it is also beneficial to form a deep and continuous sunken texture.
[0058] In another preferred embodiment of the present technical solution, the viscosity of the glaze is preferably 2000-3000 mPa·s. The above viscosity range can ensure the smoothness of the bell-shaped glaze, while ensuring that the glaze is not easy to melt flat after being fired in the kiln, which is conducive to the formation of a recessed texture layer.
[0059] Further, in step C, the specific gravity of the glaze is 1.85-1.87, and the glaze pouring amount is 448-530 g / m 2 .
[0060] In a preferred embodiment of the present technical solution, the glaze specific gravity and glaze pouring amount are controlled, so that a concave texture layer of ideal thickness can be deposited on the top of the glazed tile while ensuring the stability of the glaze pouring quality, thereby forming a deep and continuous concave texture, which is conducive to its adaptation to the glaze pouring application mode.
[0061] Further description, calculated by mass, the raw materials for the glaze include 55-60 parts of albite, 8-12 parts of dolomite, 6-10 parts of washed kaolin, 5-8 parts of strontium carbonate, 10-12 parts of quartz, 3-5 parts of zinc oxide, 4-8 parts of calcite and 1-3 parts of calcined alumina.
[0062] In a preferred embodiment of the present technical solution, by limiting the raw materials for the glaze and the amount of each raw material added, it is beneficial to form a glaze with a high silicon, high aluminum and low flux system, ensuring the low and high temperature fluidity of the glaze, which is beneficial to the formation of a deep and continuous concave texture.
[0063] Further, in step D, the mixing ratio of the dry particles, the flux and the suspending agent is (17-26): (21-33): (6-10) in terms of mass ratio.
[0064] The mixing ratio of dry particles, flux and suspending agent is preferably (17-26): (21-33): (6-10), which is conducive to ensuring that the dry particle glaze can effectively improve the depth of the concave texture and the continuity of the lines, as well as the hardness and wear resistance of the glaze surface, while also ensuring that the glaze surface has good transparency, color development and anti-fouling properties. At the same time, since the dry particles are coarse and have a large specific gravity, they are prone to precipitation. A certain proportion of suspending agent needs to be added to the glaze slurry of the dry particle glaze for suspension and dispersion, so as to effectively ensure the stability of the performance of the dry particle glaze slurry and be suitable for glaze spraying operation.
[0065] Further, in step D, the dry particles include quartz, corundum and alumina; the flux includes potassium feldspar, wollastonite, zinc oxide and barium carbonate; the suspending agent includes washed kaolin;
[0066] Calculated by weight, the raw materials of the dry granular glaze include 13 to 18 parts of quartz, 1 to 3 parts of corundum, 3 to 5 parts of aluminum oxide, 6 to 10 parts of washed kaolin, 36 to 42 parts of potassium feldspar, 15 to 20 parts of wollastonite, 6 to 10 parts of zinc oxide and 0 to 3 parts of barium carbonate.
[0067] Since quartz, corundum and alumina all have high hardness and wear resistance, they still exist in the form of complete particles after firing, thereby reducing the impact on the color of the dry granular glaze and further ensuring that the product has good transparency.
[0068] In addition, potassium feldspar, wollastonite, zinc oxide and barium carbonate all have the characteristics of lowering the glaze temperature and promoting the melting of the glaze to form glass. Therefore, the technical solution uses potassium feldspar, wollastonite, zinc oxide and barium carbonate as fluxes to ensure the transparency and antifouling properties of the dry granular glaze layer obtained by the dry granular glaze. In addition, barium carbonate can also adjust the expansion coefficient of the dry granular glaze, which is beneficial to reduce the stress difference between the dry granular glaze layer and other layers, and ensure the adhesion firmness of the dry granular glaze layer.
[0069] Further, in step D, the specific gravity of the dry granular glaze is 1.20-1.25, and the spraying amount of the glaze is 122-163 g / m 2 .
[0070] In a preferred embodiment of the present technical solution, the specific gravity of the dry granular glaze is controlled, which is beneficial to improve the uniformity of spraying, form an ideal atomization effect, and improve the aesthetics and performance of the glaze surface. In addition, when the spraying amount of the dry granular glaze exceeds 163g / m 2 The dry particle glaze layer formed is too thick, which can easily block other glaze layers and reduce the transparency and layering of the glaze surface.
[0071] Further, in step D, the specific method of the full polishing treatment is: firstly, the surface of the glazed tile is roughly polished using the diamond grinding block group I, then the surface of the glazed tile is medium polished using the diamond grinding block group II, and finally the surface of the glazed tile is finely polished using the diamond grinding block group III;
[0072] Among them, the weight of the corundum grinding blocks in the corundum grinding block group I is greater than the weight of the corundum grinding blocks in the corundum grinding block group II, and the weights of the corundum grinding blocks in the corundum grinding block group II and the corundum grinding block group III are the same; the mesh number of the corundum grinding blocks in the corundum grinding block group I is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group II, and the mesh number of the corundum grinding blocks in the corundum grinding block group II is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group III.
[0073] The diamond abrasive blocks in diamond abrasive block group I are heavier and have smaller meshes, which are beneficial for providing stronger cutting force and faster material removal rate in the rough polishing stage, helping to quickly remove the rough layer and deep scratches on the surface of the glazed tile and improve the initial flatness of the surface.
[0074] As the polishing process progresses, the use of lighter corundum grinding blocks can reduce the pressure on the surface of the glazed tile, avoid causing new damage while removing surface scratches, ensure the smooth progress of the polishing process, and ensure the quality of the glaze after polishing. Therefore, the weight of the corundum grinding blocks in corundum grinding block group II and corundum grinding block group III is less than the weight of the corundum grinding blocks in corundum grinding block group I.
[0075] Furthermore, the mesh number of the corundum grinding blocks in corundum grinding block group II is larger than that of the corundum grinding blocks in corundum grinding block group I, and the mesh number of the corundum grinding blocks in corundum grinding block group II is smaller than that of the corundum grinding blocks in corundum grinding block group III, that is (corundum grinding blocks with medium mesh number are used in the medium polishing stage), which can further refine the glaze surface of the glazed tile, remove the tiny scratches and unevenness left in the rough polishing stage, make the glaze surface smoother and more delicate, and prepare for the fine polishing stage.
[0076] Since the larger the mesh number of the corundum grinding block, the finer its particle size, therefore, the corundum grinding block in the corundum grinding block group III has the largest mesh number, which can further refine the glaze surface of the glazed tile, remove the tiny flaws left in the middle polishing stage, make the glaze surface reach a mirror effect, and improve the gloss and beauty of the glazed tile.
[0077] At the same time, in this technical solution, the diamond grinding block group I, diamond grinding block group II and diamond grinding block group III cooperate with each other, so that the polishing depth is appropriate, avoiding too deep polishing, which easily causes the lines of the concave texture to be polished away, and also avoiding too shallow polishing, which easily causes missed polishing and affects the mirror effect of the glaze. That is, in this technical solution, diamond grinding block group I, diamond grinding block group II and diamond grinding block group III cooperate with each other, and on the premise of obtaining a deep and continuous texture, the polished glaze surface also ensures that the mirror effect is achieved, thereby improving the gloss and aesthetics of the glazed tile.
[0078] Further, in step D, the diamond grinding block group I includes 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 220 to 240, 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 280 to 300, and 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 380 to 400;
[0079] The diamond grinding block group II includes 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 550 to 600 meshes and 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 780 to 800 meshes;
[0080] The diamond grinding block group III includes 5 to 10 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1000 to 1100, 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1400 to 1500, and 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1800 to 2000.
[0081] This technical solution is conducive to achieving step-by-step polishing from coarse to fine by specifically grading the corundum grinding block group I, corundum grinding block group II and corundum grinding block group III, ensuring steady improvement in glaze quality. The combination of corundum grinding blocks with various mesh sizes provides a wider adaptability, which is more conducive to obtaining a deep and continuous texture while ensuring that the polished glaze achieves a mirror effect, thereby improving the gloss and aesthetics of the glazed tiles.
[0082] A fully polished glazed tile with deep and continuous concave texture is prepared using the above-mentioned method for preparing a fully polished glazed tile with deep and continuous concave texture. The wear resistance of the fully polished glazed tile reaches at least level 4 2100 revolutions, and the anti-fouling level reaches level 5.
[0083] The technical solution of the present invention also proposes a fully polished glazed tile prepared by the above-mentioned preparation method of the fully polished glazed tile with deep and continuous concave texture, the glaze surface of which has a deep and continuous concave-convex texture, and also has excellent hardness and wear resistance, and the wear resistance of the fully polished glazed tile reaches at least level 4 2100 revolutions, and the anti-fouling level reaches level 5.
[0084] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0085] Performance Testing:
[0086] Glaze effect: Observe the glaze effect with the naked eye.
[0087] Wear resistance determination: Wear resistance: The wear resistance of the product glaze is tested using the test method of "GB / T3810.7-2016 Ceramic Tile Test Method Part 7: Determination of Surface Wear Resistance of Glazed Tile", and the wear resistance reaches at least level 4 2100 revolutions.
[0088] Antifouling test: Use the test method of GB / T 3810.14-2016 "Test methods for tiles Part 14 Determination of stain resistance Building materials standard" and use the green dye in light oil as the stain agent to test the stain resistance of the product glaze. The stain resistance is divided into 1-5 levels according to the difficulty of cleaning. The higher the level, the better the stain resistance.
[0089] Hardness: Use a Mohs hardness tester to test the Mohs hardness of glazed tiles.
[0090] Example 1
[0091] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0092] B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer;
[0093] C. Sprinkle glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the glaze includes SiO2 63%, Al2O3 14%, CaO 5%, MgO 1%, K2O 0.5%, Na2O 5%, BaO1%, SrO 4% and ZnO 4%, and the rest is the loss on ignition; the raw materials of the glaze include 55 parts of albite, 10 parts of dolomite, 8 parts of washed kaolin, 7 parts of strontium carbonate, 11 parts of quartz, 4 parts of zinc oxide, 6 parts of calcite and 2 parts of calcined alumina; according to mass percentage, the glaze passes through a 250-mesh sieve, the sieve residue is 0.3%, and the viscosity is 2500Pa·s; the specific gravity of the glaze is 1.87, and the glaze spraying amount is 510g / m 2 ;
[0094] D. Spray dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include 16 parts of quartz, 2 parts of corundum, 4 parts of aluminum oxide, 8 parts of washed kaolin, 40 parts of potassium feldspar, 18 parts of wollastonite, 8 parts of zinc oxide and 1 part of barium carbonate; the specific gravity of the dry granular glaze is 1.22, and the spraying amount is 148g / m 2 ;
[0095] E. After drying, the tiles are fired in a kiln and fully polished to obtain fully polished glazed tiles; wherein the specific method of the full polishing treatment is: firstly, the surface of the glazed tiles is roughly polished by using a diamond grinding block group I, then the surface of the glazed tiles is medium polished by using a diamond grinding block group II, and then the surface of the glazed tiles is finely polished by using a diamond grinding block group III; the diamond grinding block group I includes 15 groups of diamond grinding blocks with a weight of 3 kg and a mesh number of 240, 15 groups of diamond grinding blocks with a weight of 3 kg and a mesh number of 300, and 15 groups of corundum grinding blocks weighing 3kg and having a mesh number of 400; corundum grinding block group II includes 7 groups of corundum grinding blocks weighing 2kg and having a mesh number of 600 and 7 groups of corundum grinding blocks weighing 2kg and having a mesh number of 800; corundum grinding block group III includes 7 groups of corundum grinding blocks weighing 2kg and having a mesh number of 1000, 6 groups of corundum grinding blocks weighing 2kg and having a mesh number of 1500 and 6 groups of corundum grinding blocks weighing 2kg and having a mesh number of 2000.
[0096] Example 2
[0097] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0098] B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer;
[0099] C. Apply polishing glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the polishing glaze includes SiO2 62%, Al2O3 13%, CaO 6%, MgO 1%, K2O 0.5%, Na2O 6%, BaO1%, SrO 3% and ZnO 4%, and the rest is the loss on ignition; the raw materials of the polishing glaze include 55 parts of albite, 8 parts of dolomite, 10 parts of washed kaolin, 5 parts of strontium carbonate, 10 parts of quartz, 4 parts of zinc oxide, 6 parts of calcite and 3 parts of calcined alumina; according to mass percentage, the polishing glaze passes through a 250-mesh sieve, the sieve residue is 0.4%, and the viscosity is 2000mPa·s; the specific gravity of the polishing glaze is 1.85, and the amount of glaze applied is 530g / m 2 ;
[0100] D. Spray dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include 18 parts of quartz, 2 parts of corundum, 4 parts of aluminum oxide, 6 parts of washed kaolin, 40 parts of potassium feldspar, 20 parts of wollastonite, 8 parts of zinc oxide and 3 parts of barium carbonate; the specific gravity of the dry granular glaze is 1.25, and the spraying amount is 160g / m 2 ;
[0101] E. After drying, the tiles are fired in a kiln and fully polished to obtain fully polished glazed tiles; wherein the specific method of the full polishing treatment is: firstly, the surface of the glazed tiles is roughly polished by using a diamond grinding block group I, then the surface of the glazed tiles is medium polished by using a diamond grinding block group II, and then the surface of the glazed tiles is finely polished by using a diamond grinding block group III; the diamond grinding block group I includes 12 groups of diamond grinding blocks with a weight of 3kg and a mesh number of 220, 12 groups of diamond grinding blocks with a weight of 3kg and a mesh number of 300, and 12 groups of diamond grinding blocks with a weight of 3kg and a mesh number of 1200. The invention discloses a diamond grinding block group comprising 12 groups of diamond grinding blocks with a weight of 3 kg and a mesh number of 380; the diamond grinding block group II includes 10 groups of diamond grinding blocks with a weight of 2 kg and a mesh number of 550 and 10 groups of diamond grinding blocks with a weight of 2 kg and a mesh number of 780; the diamond grinding block group III includes 5 groups of diamond grinding blocks with a weight of 2 kg and a mesh number of 1100, 5 groups of diamond grinding blocks with a weight of 2 kg and a mesh number of 1500 and 5 groups of diamond grinding blocks with a weight of 2 kg and a mesh number of 1800.
[0102] Example 3
[0103] A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying;
[0104] B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer;
[0105] C. Apply polishing glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the polishing glaze includes SiO2 65%, Al2O3 16%, CaO 4%, MgO 1%, K2O 0.5%, Na2O 4%, BaO1%, SrO 3% and ZnO 3%, and the rest is the loss on ignition; the raw materials of the polishing glaze include 60 parts of albite, 8 parts of dolomite, 6 parts of washed kaolin, 5 parts of strontium carbonate, 10 parts of quartz, 3 parts of zinc oxide, 8 parts of calcite and 3 parts of calcined alumina; according to mass percentage, the polishing glaze passes through a 250-mesh sieve, the sieve residue is 0.5%, and the viscosity is 3000mPa·s; the specific gravity of the polishing glaze is 1.87, and the glaze amount is 450g / m 2 ;
[0106] D. Spray dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include 18 parts of quartz, 1 part of corundum, 3 parts of aluminum oxide, 10 parts of washed kaolin, 36 parts of potassium feldspar, 20 parts of wollastonite, 6 parts of zinc oxide and 2 parts of barium carbonate; the specific gravity of the dry granular glaze is 1.20, and the spraying amount is 130g / m 2 ;
[0107] E. After drying, the tiles are put into a kiln for firing, and fully polished to obtain fully polished glazed tiles; wherein the specific method of the full polishing treatment is: firstly, the surface of the glazed tiles is roughly polished by using a diamond grinding block group I, then the surface of the glazed tiles is medium polished by using a diamond grinding block group II, and then the surface of the glazed tiles is finely polished by using a diamond grinding block group III; the diamond grinding block group I includes 10 groups of diamond grinding blocks with a weight of 3 kg and a mesh number of 220, 10 groups of diamond grinding blocks with a weight of 3 kg and a mesh number of 300, and There are 10 groups of corundum grinding blocks weighing 3kg and having a mesh number of 400; the corundum grinding block group II includes 5 groups of corundum grinding blocks weighing 2kg and having a mesh number of 550 and 5 groups of corundum grinding blocks weighing 2kg and having a mesh number of 800; the corundum grinding block group III includes 8 groups of corundum grinding blocks weighing 2kg and having a mesh number of 1000, 8 groups of corundum grinding blocks weighing 2kg and having a mesh number of 1400 and 8 groups of corundum grinding blocks weighing 2kg and having a mesh number of 2000.
[0108] Comparative Example 1
[0109] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that no dry particle glaze layer is provided in Comparative Example 1.
[0110] Comparative Example 2
[0111] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that a glaze with a higher high-temperature viscosity is used in Comparative Example 2.
[0112] The glazed tiles obtained in the above embodiments and comparative examples were subjected to performance tests, and the specific test results are shown in the following table:
[0113]
[0114] From the performance test results of each embodiment in Table 1 above, it can be seen that a glazed tile prepared from a fully polished glazed tile with a deep and continuous concave texture has a glaze surface with a deep and continuous concave-convex texture, and also has excellent hardness and wear resistance. The wear resistance of the fully polished glazed tile reaches at least level 4 2100 revolutions, and the anti-fouling level reaches at least level 5, which meets actual use requirements.
[0115] Comparative Example 1 has a slightly shallower concave depth, a slightly broken texture line, and reduced transparency due to the lack of a dry granular glaze layer. In addition, the hardness, wear resistance, and antifouling properties of the material are reduced due to the lack of a dry granular glaze layer.
[0116] In Comparative Example 2, since the polishing glaze with relatively high high-temperature viscosity is used, the formed concave texture is easily melted flat, resulting in shallow concave texture and discontinuous lines.
[0117] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a fully polished glazed tile with a deep and continuous concave texture, characterized in that: The following steps are involved: A. preparing a ceramic blank, pressing the ceramic blank, and obtaining a green body after drying; B. Printing mold ink on the surface of the blank according to a preset pattern to form a mold ink layer; C. Sprinkling polishing glaze on the surface of the mold ink layer to form a concave texture layer; wherein, calculated by mass percentage, the chemical composition of the polishing glaze includes SiO2 62-66%, Al2O3 13-16%, CaO 4-7%, MgO 0-2%, K2O 0-1%, Na2O 4-6%, BaO 0-2%, SrO 3-5% and ZnO 3-5%, and the rest is ignition loss; D. spraying dry granular glaze on the surface of the concave texture layer to form a dry granular glaze layer; the raw materials of the dry granular glaze include dry granules, flux and suspending agent; E. After drying, put it into the kiln for firing, and after full polishing, you can get fully polished glazed tiles.
2. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step C, the glaze is passed through a 250-mesh sieve, the residue is 0.3-0.5% and the viscosity is 2000-3000 mPa·s according to mass percentage.
3. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step C, the specific gravity of the glaze is 1.85-1.87, and the glaze pouring amount is 448-530 g / m 2 .
4. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: Calculated by weight, the raw materials for the glaze include 55-60 parts of albite, 8-12 parts of dolomite, 6-10 parts of washed kaolin, 5-8 parts of strontium carbonate, 10-12 parts of quartz, 3-5 parts of zinc oxide, 4-8 parts of calcite and 1-3 parts of calcined alumina.
5. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step D, the mixing ratio of the dry particles, the flux and the suspending agent is (17-26): (21-33): (6-10) in terms of mass ratio.
6. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step D, the dry particles include quartz, corundum and alumina; the flux includes potassium feldspar, wollastonite, zinc oxide and barium carbonate; and the suspending agent includes washed kaolin; Calculated by weight, the raw materials of the dry granular glaze include 13 to 18 parts of quartz, 1 to 3 parts of corundum, 3 to 5 parts of aluminum oxide, 6 to 10 parts of washed kaolin, 36 to 42 parts of potassium feldspar, 15 to 20 parts of wollastonite, 6 to 10 parts of zinc oxide and 0 to 3 parts of barium carbonate.
7. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step D, the specific gravity of the dry granular glaze is 1.20-1.25, and the spraying amount of the glaze is 122-163 g / m 2 .
8. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 1, characterized in that: In step D, the specific method of the full polishing treatment is: firstly, the surface of the glazed tile is roughly polished by using the diamond grinding block group I, then the surface of the glazed tile is medium polished by using the diamond grinding block group II, and finally the surface of the glazed tile is finely polished by using the diamond grinding block group III; Among them, the weight of the corundum grinding blocks in the corundum grinding block group I is greater than the weight of the corundum grinding blocks in the corundum grinding block group II, and the weights of the corundum grinding blocks in the corundum grinding block group II and the corundum grinding block group III are the same; the mesh number of the corundum grinding blocks in the corundum grinding block group I is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group II, and the mesh number of the corundum grinding blocks in the corundum grinding block group II is smaller than the mesh number of the corundum grinding blocks in the corundum grinding block group III.
9. The method for preparing a fully polished glazed tile having a deep and continuous concave texture according to claim 8, characterized in that: In step D, the diamond grinding block group I includes 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 220 to 240, 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 280 to 300, and 10 to 15 groups of diamond grinding blocks weighing 3 kg and having a mesh number of 380 to 400; The diamond grinding block group II includes 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 550 to 600 meshes and 5 to 10 groups of diamond grinding blocks weighing 2 kg and having a mesh number of 780 to 800 meshes; The diamond grinding block group III includes 5 to 10 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1000 to 1100, 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1400 to 1500, and 5 to 8 groups of diamond grinding blocks weighing 2kg and having a mesh number of 1800 to 2000.
10. A fully polished glazed tile with deep and continuous concave texture, characterized in that: The fully polished glazed tile is prepared by the preparation method of any one of claims 1 to 9 having a deep and continuous concave texture, wherein the wear resistance of the fully polished glazed tile reaches at least level 4 at 2100 revolutions, and the anti-fouling level reaches level 5.
Citation Information
Patent Citations
Preparation method of ceramic tile with numerical control mold effect
CN113183292A
Pattern mold texture brick with clear mold texture and preparation process thereof
CN113526869A
High-transparency ceramic rock plate with deep concave-convex textures and preparation method of high-transparency ceramic rock plate
CN114804824A
Wear-resistant glazed brick with good color development, strong transparency and high hardness and preparation process thereof
CN115536272A
Production process for positionally stripped dry particle ceramic tile, and product thereof
WO2024037052A1
Cited By
Ceramic tile polishing method
CN120461197A
